TRANSAKSI JUAL BELI SAMPAH DALAM PERSPEKTIF HUKUM PERLINDUNGAN KONSUMEN (Studi pada Koperasi Bank Sampah Sunggal Mandiri, Paya Bakung Kabupaten Deli Serdang) - Debora; Divo Anantama (LPPM Universitas HKBP Nommensen, 2021)
Waste management efforts in North Sumatra are carried out in various ways, including through the Waste Bank program. Saving waste in the waste bank is carried out by buying and selling waste. The type of research used is empirical legal research. The practice of buying and selling waste at the Sunggal Mandiri Garbage Bank with residents, namely in the collection, management, and utilization of waste, where the community directly contributes to the collection and sorting of waste, while the Garbage Bank is tasked with managing waste so that waste can be disposed of. In article 4 paragraph 1 of the Consumer Protection Act No. 8 of 1999, consumers or property buyers have rights including comfort, security and safety in consuming products and services and choosing them according to the exchange rate and conditions according to the agreement.